Healthcare utilization, psychiatric medication and risk of rehospitalization in suicide-attempting patients with common mental disorders. (April 2020) - Niederkrotenthaler, Thomas; Mittendorfer-Rutz, Ellenor; Thurner, Stefan; Endel, Gottfried; Klimek, Peter
Objective: Common mental disorders are strong risk factors for suicide attempt. We compared common mental disorder patients with and without suicide attempt regarding health care utilization and psychiatric medication, assessed gender differences and identified how psychotropic medication of attempters is associated with subsequent rehospitalization. Methods: We used administrative claims data of 22, 276 common mental disorder patients with inpatient care in Lower Austria between 1 January 2006 and 31 December 2011. Suicide attempters (cases, n = 615) and non-attempters (controls, n = 21, 661) were compared regarding specific healthcare utilization by calculating mean differences of time-dependent contact probabilities and psychiatric medication (i.e. prescribed defined daily doses) ± 0.5 years around their suicide attempt (cases)/common mental disorder diagnosis (controls). Cluster analysis was used to group suicide attempters according to their psychiatric medication. The risk of rehospitalization 0.5–3 years after the attempt was calculated with regression analysis controlling for sex, age and morbidity-related factors. Results: Contacts with general practitioners were lower for attempters than non-attempters (mean difference of contact probabilities over observation period, males = −0.05, 95% confidence interval = [−0.07, −0.03]; females: mean difference = −0.04, 95% confidence interval = [−0.05, −0.03]). Regarding psychiatrists, female attempters had markedly higher contact probabilities after the attempt compared to female non-attempters (mean difference = 0.02, 95% confidence interval = [0.007, 0.04]); male attempters had lower contact probabilities before the attempt compared to male non-attempters (mean difference = −0.01, 95% confidence interval = [−0.004, −0.02]). Attempters had higher dosages of psychiatric medication across the entire period. Antidepressant and antipsychotic medication peaked at the time of common mental disorder diagnosis/attempt. Benzodiazepine prescriptions were considerably higher for male attempters than their female counterparts and were constantly elevated for male attempters across the observation period. A cluster of attempters with long-term benzodiazepine prescriptions had an increased risk of rehospitalization (adjusted odds ratio = 2.4, 95% confidence interval = [1.1, 5.5]). Conclusion: Despite lower contact probabilities, common mental disorder patients with suicide attempt are prescribed more psychiatric medication, particularly benzodiazepines, with an elevated risk of rehospitalization. Strong sex differences were found.